Mobile plants for plasma chemical water treatment - Bruyako Michail; Grigoreva Larisa (MATEC Web of Conferences, 2018)
Water is a valuable natural resource. It provides an exceptional role in metabolic processes, which are the basis of life. The negative factor of human activity is pollution of the environment, including water resources. Municipal sewage treatment is an urgent environmental problem. It exists both in Russia and abroad. Despite all the measures and methods used to treat wastewater, pollutants continue to flow into water bodies. The most dangerous pollutants are heavy metals, organic substances (proteins, fats, carbohydrates). To solve this problem, both traditional and modern methods are proposed. The purpose of this study is to develop an energy-efficient, eco-friendly mobile device for water purification based on the action of low-temperature nonequilibrium plasma. The developed installation has a small weight of 20 to 50 kg, occupies a small area. To move it you can use any vehicle. Model samples and samples from the municipal sewerage network were prepared as experimental samples. The effect of low-temperature plasma showed a high degree of purification with a single exposure at low values of electric energy consumption per unit of water to be purified. Reduction of the concentration of ammonium-ion and ammonium nitrogen reaches 96-98%.